THE INFLUENCE OF CULTURE ON CHILD RIGHTS VIOLATIONS IN ZIMBABWE: A CASE STUDY - Tshugulu, Ansley Nonsikelelo; Simbine, Samuel Lisenga; Charamba, Sunungurai; Muridzo, Noel Garikai (Social Work/Maatskaplike Werk, 2023)
The article explores child rights violations emanating from harmful cultural practices in Zimbabwe. A qualitative case study research design was used. The targeted population included people considered custodians of the Ndebele culture in the Nkayi district of Zimbabwe. Social workers familiar with Ndebele culture and working in the child protection field within the Nkayi district also participated in the study. In-depth interviews were used to collect data. The data were analysed using Creswell’s thematic analysis. Whilst culture undoubtedly provides some ecological resources for the realisation of child rights, findings highlight harmful cultural practices which violate children’s rights, and these are the focus of this article.